Malaysia Between the United States and China: What do Weaker States Hedge Against?. Issue 1 (16th January 2016) - Kuik, Cheng‐Chwee
Abstract : This article analyzes Malaysia's alignment behavior vis‐à‐vis America and China, with a focus on explaining how the weaker state's insistence on hedging has both motivated and limited its defense links with the competing powers. Contrary to the conventional wisdom that regional states choose to align militarily with the rebalancing America to hedge against China, the article argues that this characterization is only partially true; a more accurate account is that weaker states do not hedge against any single actor per se; rather, they seek to hedge against a range of risks associated with uncertain power relations. In the case of Malaysia, while Putrajaya aims to mitigate the challenges of an assertive Beijing, its alignment behavior is more a function of a desire to offset several systemic and domestic risks, namely, the shadow of entrapment, abandonment, and alienation, alongside the fear of authority erosion at home.